Algorithmic Entities - Lynn M. LoPucki (Washington University Law Review, 2018)
In a 2014 article, Professor Shawn Bayern demonstrated that anyone can confer legal personhood on an autonomous computer algorithm by putting it in control of a limited liability company. Bayern’s demonstration coincided with the development of “autonomous” online businesses that operate independently of their human owners—accepting payments in online currencies and contracting with human agents to perform the off-line aspects of their businesses. About the same time, leading technologists Elon Musk, Bill Gates, and Stephen Hawking said that they regard human-level artificial intelligence as an existential threat to the human race. This Article argues that algorithmic entities—legal entities that have no human controllers—greatly exacerbate the threat of artificial intelligence. Algorithmic entities are likely to prosper first and most in criminal, terrorist, and other anti-social activities because that is where they have their greatest comparative advantage over human-controlled entities. Control of legal entities will contribute to the threat algorithms pose by providing them with identities. Those identities will enable them to conceal their algorithmic natures while they participate in commerce, accumulate wealth, and carry out anti-social activities. Four aspects of corporate law make the human race vulnerable to the threat of algorithmic entities. First, algorithms can lawfully have exclusive control of not just American LLC’s but also a large majority of the entity forms in most countries. Second, entities can change regulatory regimes quickly and easily through migration. Third, governments— particularly in the United States—lack the ability to determine who controls the entities they charter and so cannot determine which have non-human controllers. Lastly, corporate charter competition, combined with ease of entity migration, makes it virtually impossible for any government to regulate algorithmic control of entities.
Keywords: Artificial; Computer; Algorithm; Algorithmic Entities; Legal Entity; Intelligence; LLC; Control; Commerce; Corporate; Corporation; Human-exclusion principle; Mobility problem; Beneficial owners; Incorporator; Disclosure; Model Business; Corporate Act; Corporate Law; Corporate Governance; Competition; Limited Liability Company; Autonomy; Criminal Law; Anonymous Entities; Charter; Privacy; AE